Heating Effects of Microwave Radiation on Disposable Materials in the Presence of Various Soaking Media - Basim Mahdi, Ali; A. Mousa AL-Ibraheemi, Zahraa; K. Alhareeb, Nadeem (University of Thi-Qar Journal of Science, 2019)
The ability of various soaking media in enhancing the temperature of waste materials, once they are exposed to microwaves has been investigated. Such information helps development of microwave techniques to destroy viruses, spores and other microorganisms by temperature enhancement if they may not be affected by microwave radiation itself. Oily media were observed to have higher elevation in temperature; however, they have the inherent drawback of sticking into the inner surface of the container. Such drawbacks can be minimized by using enclosed non-stick container for the microwave application. Among aqueous fluids, commonly found detergent solution showed the best performance in raising the temperature. Such material has many other advantages such as, low cost, non-toxic nature, environment friendliness, ready availability etc.